STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALITAS DAN KINERJA GURU DI MI MA'ARIF BENDOSARI SAPURAN - Dwinanto, Arif; Muntaqo, Rifqi; El Syam, Robingun Suyud (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2023)
This research is to analyze the strategy of the madrasah principal in improving the professionalism and performance of teachers at MI Ma'arif Bendosari Sapuran. This paper is the result of descriptive qualitative field research with data collection techniques: observation, interviews, and documentation, then analyzed descriptively. The research results show that the madrasah principal's strategy to improve teacher professionalism and performance at MI Ma'arif Bendosari Sapuran includes three steps: 1) Creating policies aimed at improving teacher professionalism and performance; 2) Placing teachers based on their background and expertise to ensure they are able to carry out their duties effectively and adapt easily; 3) Implementing punishment and rewards to encourage teachers to continue to improve discipline and maintain morale, because they are role models for their students. This strategy is implemented through the implementation of teacher training and development programs, placing prospective teachers according to their educational background, expertise, and experience, and giving reprimands to teachers who lack discipline. This implementation is supported by an adequate Madrasah IT system and the familiarity of the madrasah community. This strategy has implications for the ability of teachers to apply the knowledge gained during training and improve student achievement. Achievements show that all madrasah members have a high sense of responsibility and concern, thus making MI Ma'arif Bendosari Sapuran a leading madrasah and able to compete with other madrasahs in Wonosobo Regency